Deceptive Brown Adipose Tissue - Payra, Biswajit; Dhar, Abhranil; Singhania, Pankaj; Khatri, Akshay; Sahana, Pranab Kumar (Journal of the ASEAN Federation of Endocrine Societies, 2024)
A 23-year-old female presented with headache, palpitation, and hypertensive spells. There was no similar family history. Twenty-four (24) hour urine testing showed elevated normetanephrine level with normal metanephrines [metanephrines 123 mcg/24 hrs (74-297); normetanephrines 5321.16 mcg/24 hrs (73-808)]. A biochemical diagnosis of normetanephrine-secreting pheochromocytoma was made. Considering the age and urine reports, a functional scan was ordered. Imaging with 18-FDG PET CT was done which showed uptake indicative of a large left adrenal mass, as well as uptake in the mediastinal, abdominopelvic, lymph nodes and metabolically active mesenteric, peritoneal and omental thickness. This suggested a left adrenal pheochromocytoma with the possibility of an associated lymphoproliferative disorder or active lesions in brown fat. To describe these extra-adrenal lesions, a Ga-68 This work DOTANOC PET CT was obtained which showed a diffuse somatostatin receptor-expressing large soft tissue mass lesion in the left adrenal likely to be pheochromocytoma without any other lesion elsewhere in the whole body survey. This depicts the confusion created by the metabolically active brown adipose tissue (BAT) in the FDG PET scan. Brown fat is involved in non-shivering thermogenesis and is typically located in the cervical, supraclavicular, mediastinal, and abdominal regions. High uptake in the BAT can make interpretation of the FDG PET report difficult and misleading. Some precautions like avoidance of cold and beta blockers can minimize BAT uptake in FDGPET scans.